PARPi after PARPi in epithelial ovarian cancer - K.G. Essel; K. Behbakht; T. Lai; L. Hand; E. Evans; J. Dvorak; K. Ding; G. Konecny; K.N. Moore (Elsevier, 2021)
The objective of this study was to describe the treatment experience of patients with recurrent epithelial ovarian cancer who are retreated with an inhibitor of poly(ADP-ribose)-polymerase (PARPi). We conducted a multi-institutional, retrospective review of ovarian cancer patients who received ≥2 lines of therapy containing a PARPi. Demographic, clinical, and pathological data were analyzed with descriptive statistics. Twenty-two patients were identified. For initial PARPi (PARPi1), 12 patients (54.5%) received veliparib, 7 (31.8%) olaparib and 3 (13.6%) rucaparib resulting in 10 patients who had no evidence of disease at the completion of therapy (NED), 3 partial responses (PR), 4 stable disease (SD), and 3 progressive disease (PD). (All 10 CRs involved veliparib given in conjunction with cytotoxic chemotherapy). PARPi1 was used as maintenance in 2 patients. PARPi1 was discontinued because planned number of cycles was reached (n = 10), progression (n = 8), toxicity (n = 2), other (n = 2). For second PARPi (PARPi2), 10 patients (45.4%) received niraparib, 6 (27.3%) olaparib, and 6 (27.3%) rucaparib resulting in 3 PR, 13 SD, and 3 PD. PARPi2 was used as maintenance in 3 patients. The 3 patients who experienced a PR to PARPi2 had a BRCA mutation and were NED following PARPi1. PARPi2 was discontinued because of progression (n = 13), toxicity (n = 6), other (n = 2). One patient currently remains on PARPi2. Toxicity after PARPi1 was not associated with toxicity from PARPi2 (p > 0.05). With 3 approved PARPi for different indications including frontline and recurrence, the opportunity to reuse PARPi has increased. Characterizing those who should be re-challenged is an important initiative moving forward.